Increasing Students' Vocabulary Mastery by Using Stand Up Sequences Game - Hisnairah Nasmawi; Nanning (Institut Agama Islam Negeri Parepare, 2021)
This research to find out the whether or not the increasing of vocabulary by using stand up sequences game at the second year students’ of MA-Al Amanah Waikaya Kab Mamuju Tengah. In this research, the researcher used pre-experimental method with two objects pre-test and post- test design. The instruments of collecting data used in this research was translation, matching and multiple choice. The population was at the second year students of MA-Al Amanah Waikaya Kab. Mamuju Tengah with total number of student 60 students. But the researcher took XIB. Class as the sample that was taken by using random sampling. Thus, the number of sample were 24 students. They were giving treatment about vocabulary by using stand up sequences game. The result of the research showed the mean score of pre-test was 60,25 and the mean score of post-test was 88,95.while the t-test was greater than the t-table(11,93> 2.064). It showed that the H0 hypothesis was rejected and the H1 hypothesis was accepted. The conclusion is Stand up Sequences game is effective to Increase Students’ Vocabulary Mastery by Using Stand up Sequences Game at the Second Year Students’ of MA- Al Amanah Waikaya Kab Mamuju Tengah.